The Role of Rumination as a Maladaptive Coping Mechanism in Cases of Comprehensive Anxiety Disorder - Osya Azifa Firlani; Hafid Algristian; Budi Cahyono (Psychosocia : Journal of Applied Psychology and Social Psychology, 2026)
Generalized Anxiety Disorder (GAD) is characterized by excessive and persistent worry accompanied by somatic and cognitive symptoms that impair daily functioning. Although rumination has been widely discussed as a form of repetitive negative thinking, its role as a maladaptive coping mechanism sustaining GAD relapse in the context of occupational stress and shift work remains underexplored. This study presents an analytical descriptive case study integrated with a narrative literature review to examine how rumination contributes to symptom maintenance and relapse in GAD. The case involves a 43-year-old female outpatient evaluated at a psychiatric clinic in Surabaya in 2025. The recurrence of anxiety symptoms was precipitated by an early-retirement offer and rotating shift work, which triggered persistent rumination about financial uncertainty. This cognitive process led to insomnia, concentration difficulties, and inconsistent medication adherence, ultimately resulting in symptom relapse. Literature-based interpretation suggests that intolerance of uncertainty (IU) increases vulnerability to rumination, which sustains autonomic hyperarousal and sleep disturbance, while shift work disrupts circadian rhythms and contributes to inconsistent dosing and fluctuating plasma levels of pharmacotherapy. This case highlights a clinically relevant pathway linking occupational uncertainty, rumination, insomnia, and nonadherence in GAD relapse. Comprehensive management should integrate pharmacotherapy, rumination-focused psychotherapy (e.g., CBT or MCT), adherence education, and consideration of workplace-related stressors to reduce recurrence risk.